A new species of Helvella (Helvellaceae, Pezizomycetes) within the H. macropus group from China - Lu, Jin-Rong; Yu, Feng-Ming; Lei, Lei; Zhang, Ying; Zhao, Qi (Phytotaxa, 2023)
The brown cupulate saddle fungi with villus surface in China, have long been named as Helvella macropus, a well-known European and North American species. In this study, Helvella fruiting bodies from Austria, China (the Tibetan Plateau), and Germany were examined. Phylogenetic analyses of combined LSU, TEF and HSP90 sequence data showed that the Chinese H. macropus-like samples represent two phylogenetic species, one of which is H. macropus s.s., and the other is H. guttata, which is introduced as new species here. Helvella guttata and H. macropus are described and illustrated in detail and compared with their similar species. In addition, a key to the morphologically recognizable taxa of the H. macropus complex is provided.